Exploring Children's Literature Content in Indonesian Textbooks for Elementary Schools: Insights from the Merdeka Curriculum - Haqi, Salisa Arina; Wibowo, Setiawan Edi; Hastuti, Woro Sri; Wuriyandani, Wuri; Fauziah, Muhardila (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the representation and quality of children’s literature content in Indonesian language textbooks for elementary schools under the Merdeka Curriculum, a national education policy aimed at promoting student-centered learning. With particular attention to genre diversity, developmental appropriateness, and alignment with literacy goals, this research examines the extent to which these textbooks provide meaningful and engaging literary experiences for students. A qualitative content analysis method was employed, focusing on textbooks for Grades I–VI published by the Indonesian Ministry of Education in 2023. This study employs qualitative content analysis of Indonesian language textbooks for elementary schools under the Merdeka Curriculum. Data were collected through document analysis using rubrics, checklists, and BSNP-based indicators. The analysis followed Miles and Huberman’s model, with validation ensured through triangulation and peer discussion. The findings indicate that literary texts are presented in various forms, including prose (fiction and nonfiction) and poetry, with realistic fiction being the most dominant genre across all grades. Lower-grade textbooks primarily feature realistic fiction and fables, while upper-grade textbooks increasingly include nonfiction texts. The alignment between literary content and learning outcomes is reflected in the variety of genres and topics relevant to students’ developmental and social contexts. These results highlight the importance of designing textbooks that not only support language skills but also foster literary appreciation and character development through contextual and meaningful texts. The study's outcomes are expected to contribute to the development of more effective and engaging Indonesian language textbooks, ultimately enhancing the quality of literacy education in Indonesian elementary schools.